Using Target-Story Picture to Improve Students’ Narrative Monologue Skill - misianto misianto (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2017)
In learning English, a narrative monologue skill is required. This is instructed by the English Curriculum of Senior High School. The existing method of narrative monologue learning implemented so far is memorization which is difficult for students to develop and to improve their own ideas. This Classroom Action Research was aimed at developing an innovative learning model of narrative monologue by using a Target-Story Picture media for improving the students’ narrative monologue skills. Based on the collected data, the use of Target-Story Picture media proved effective in improving the students’ narrative monologue skills. Thus, it is suggested for English teacher especially who teach XI Grade students to use Target-Story Picture media to teach narrative monologue.